Antihipertensive drugs consumption trends: an observational study from Portugal - Teixeira Rodrigues, António (2014)
Choose an antihypertensive drug is a very complex process with several clinical and economic implications. Our aim is to describe and characterize the consumption of antihypertensive drugs in Portugal.